The Fashion Industry During the Pandemic - Bozena FRACZEK; Piotr DABROWSKI (Communications of International Proceedings, 2021)
Fashion is a very specific industry - both creative and dynamic. The results of many studies confirm and underline its importance and its influence on the economy. As the coronavirus (COVID-19) pandemic spread globally, it affected the fashion industry on a global scale, similarly to many other industries. The objective of the research is analysis of the financial and economic position of the fashion industry in the world during the pandemic, taking into account two perspectives: financial results and financial investment in the fashion industry. The results of the research show that despite the negative influence of the pandemic on the fashion industry, it remains a relatively prosperous and developing industry. Meanwhile, although the novel and constantly changing situation has caused significant threats, it has also provided new challenges and opportunities.
Keywords: Fashion Industry; Pandemic; Sustainable Growth